2021
DOI: 10.1007/s12144-021-01540-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of central auditory processes in Polish children and adolescents at the age from 7 to 16 years

Abstract: There are discrepancies in the literature regarding the course of central auditory processes (CAP) maturation in typically developing children and adolescents. The purpose of the study was to provide an overview of age – related improvement in CAP in Polish primary and secondary school students aged 7–16 years. 180 children/adolescents, subdivided into 9 age categories, and 20 adults (aged 18–24 years) performed the Dichotic Digit Test (DDT), Duration Pattern Test (DPT), Frequency Pattern Test (FPT), Gap Detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 100 publications
(222 reference statements)
2
4
1
1
Order By: Relevance
“…Instead, the VA span measure correlated with the phonological processing marker, NonwordAccuracyDiff. Although we did not predict a relationship between these two variables, a couple of other studies found that accuracy and speed on phonemic awareness tasks were related to VA span (Lassus-Sangosse, N'guyen-Morel, & Valdois, 2008;Lewandowska, Milner, Ganc, Wlodarczyk, & Skarzynski, 2014;Saksida et al, 2016).…”
Section: Discussioncontrasting
confidence: 96%
“…Instead, the VA span measure correlated with the phonological processing marker, NonwordAccuracyDiff. Although we did not predict a relationship between these two variables, a couple of other studies found that accuracy and speed on phonemic awareness tasks were related to VA span (Lassus-Sangosse, N'guyen-Morel, & Valdois, 2008;Lewandowska, Milner, Ganc, Wlodarczyk, & Skarzynski, 2014;Saksida et al, 2016).…”
Section: Discussioncontrasting
confidence: 96%
“…Nevertheless, studies have shown that lower scores in personality traits such as conscientiousness and emotional stability, compared to mothers of children with APD, may predispose them to parental burnout (Le Vigouroux, Scola, Raes, Mikolajczak, & Roskam, 2017)although agreeableness, which was at the same level in both groups, may play a protective role. Low conscientiousness and high neuroticism are also found in mothers of children with ADHD, which may possibly include mothers of children with APD, since symptoms in neurodevelopmental disorders tend to overlap (Ahmmed et al, 2014;de Wit et al, 2018;Lawton et al, 2017;Lewandowska et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Katz (2001) describes these difficulties as the inability to take full advantage of an acoustic signal, even though it is received normally in the periphery. The British Society of Audiology describes APD as being caused by abnormal brain function characterized by incorrect differentiation, separation, grouping, localization, and ordering of stimuli (de Wit et al, 2018;Lewandowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…task-oriented), w którą zaangażowane są: procesy pamięci, uwagi, językowe oraz czytanie [20]. Zaburzenia APD mogą współwystępować z zaburzeniami neurorozwojowymi takimi jak: dysleksja, ADHD, SLI, DD, ASD [20,21], zaburzeniami rozwoju mowy, języka i /lub artykulacji [18], zaburzeniami emocjonalno-społecznymi oraz trudnościami szkolnymi [22][23][24]. Interesującym wynikiem są istotne różnice występujące między matkami i ojcami w nasileniu postaw rodzicielskich w grupie rodziców dzieci z APD [30], obserwowane także w populacji ogólnej rodziców i ich dzieci [31].…”
Section: Dzieci Z Centralnymi Zaburzeniami Przetwarzania Słuchowegounclassified